2020
DOI: 10.1016/j.ijscr.2020.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Application of minimal invasive technique for thyroidectomy without remote access in locally advanced thyroid carcinoma with gross extra-thyroidal extension

Abstract: Highlights Minimally invasive thyroidectomy (MIT) is useful and famous technique that is being applied to thyroid carcinoma. MIT without remote access is useful and applicable in thyroid disease and carcinoma in terms of cost effect and cosmetic outcome. MIT without remote access can be feasible method for thyroid carcinoma with gross extra-thyroidal extension, especially, upper pole carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The modified small incision surgery reduced the traditional surgical size from 6–8 cm to about 2 cm, avoided damage to the cervical flap, muscle, blood vessel and nerve, and achieved meticulous thyroid vessel ligation. Resection of the gland lobe while retaining the original position of parathyroid gland has little effect on blood perfusion and thyroid function ( 18 20 ). The results of this study showed that the operation time, incision length and intraoperative bleeding volume of patients in the observation group were significantly lower than those of patients in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The modified small incision surgery reduced the traditional surgical size from 6–8 cm to about 2 cm, avoided damage to the cervical flap, muscle, blood vessel and nerve, and achieved meticulous thyroid vessel ligation. Resection of the gland lobe while retaining the original position of parathyroid gland has little effect on blood perfusion and thyroid function ( 18 20 ). The results of this study showed that the operation time, incision length and intraoperative bleeding volume of patients in the observation group were significantly lower than those of patients in the control group.…”
Section: Discussionmentioning
confidence: 99%